The Symptom, Cause and Repair of Workaround - Song, Daohan; Zhong, Hao; Jia, Li (2020 35th IEEE/ACM International Conference on Automated Software Engineering (ASE), 2020)
In software development, issue tracker systems are widely used to manage bug reports. In such a system, a bug report can be filed, diagnosed, assigned, and fixed. In the standard process, a bug can be resolved as fixed, invalid, duplicated or won't fix. Although the above resolutions are well-defined and easy to understand, a bug report can end with a less known resolution, i.e., workaround. Compared with other resolutions, the definition of workarounds is more ambiguous. Besides the problem that is reported in a bug report, the resolution of a workaround raises more questions. Some questions are important for users, especially those programmers who build their projects upon others (e.g., libraries). Although some early studies have been conducted to analyze API workarounds, many research questions on workarounds are still open. For example, which bugs are resolved as workarounds? Why is a bug report resolved as workarounds? What are the repairs of workarounds? In this experience paper, we conduct the first empirical study to explore the above research questions. In particular, we analyzed 221 real workarounds that were collected from Apache projects. Our results lead to some interesting and useful answers to all the above questions. For example, we find that most bug reports are resolved as workarounds, because their problems reside in libraries (24.43%), settings (18.55%), and clients (10.41%). Among them, many bugs are difficult to be fixed fully and perfectly. As a late breaking result, we can only briefly introduce our study, but we present a detailed plan to extend it to a full paper.ACM Reference Format: Daohan Song, Hao Zhong, and Li Jia. 2020. The Symptom, Cause and Repair of Workaround. In 35th IEEE/ACM International Conference on Automated Software Engineering (ASE '20), September 21-25, 2020, Virtual Event, Australia. ACM, New York, NY, USA, 3 pages. https://doi.org/10.1145/3324884.3418910